IMPLEMENTASI JUST IN TIME DALAM MENINGKATKATKAN PRODUKTIVITAS DAN EFISIENSI BIAYA PRODUKSI - Hakim, Luqman (2477 - 6165, 2015)
The purpose of Just In Time (JIT) is to increase productivity and reduce production costs by eliminating dissipation that exist in the company through continuous improvement activities, so the purpose of this study was to determine the implementation of JIT in increase productivity and cost efficiency of production in manufacturing companies. Stages research is 1) identify problems 2) The type of data used in this research is quantitative data and qualitative data, 3) the collection and processing of production data and purchase data, 4) the implementation of JIT system, 5) eliminate the dissipation and the participation of employees, 6) reduce or eliminate defective products. And the results of this study indicate that the implementation of JIT can improve company productivity and efficiency of the production costs.